High‐throughput colorimetric assays optimized for detection of ketones and aldehydes produced by microbial cell factories. Issue 9 (10th June 2022) - Kozaeva, Ekaterina; Mol, Viviënne; Nikel, Pablo I.; Nielsen, Alex Toftgaard
Summary: Randomized strain and pathway engineering are critical to improving microbial cell factory performance, calling for the development of high‐throughput screening and selection systems. To facilitate this effort, we have developed two 96‐well plate format colorimetric assays for reliable quantification of various ketones and aldehydes from culture supernatants, based on either a vanillin‐acetone reaction or the 2, 4‐dinitrophenylhydrazine (2, 4‐DNPH) reagent. The vanillin‐acetone assay enabled accurate and selective measurement of acetone titers up to 2 g l −1 in a minimal culture medium. The 2, 4‐DNPH‐based assay can be used for a wide range of aldehydes and ketones, shown here through the optimization of conditions for 15 different compounds. Both assays were implemented to improve acetone production from different substrates by an engineered Escherichia coli strain. The fast and user‐friendly colorimetric assays proposed here open the potential for iterative rounds of (automated) strain and pathway engineering and screening, facilitating the efforts towards further boosting production titers of industrially relevant ketones and aldehydes. Abstract : To facilitate high‐throughput strain screening, we have developed two 96‐well plate format colorimetric assays for reliable quantification of various ketones and aldehydes from culture supernatants. The assays were implemented to investigate acetone production by an engineered Escherichia coli strain, highlighting their potential for use in strain and pathway engineering.